Efektivitas Komunikasi Pemasaran Benih Padi Produksi Koperasi KUAT Subak Guama - WIRTAWAN, I GEDE WEDA; SUARDI, I DEWA PUTU OKA; SARJANA, I MADE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
Effectiveness of Marketing Communication for KUAT Cooperative Production of Rice Seedsat Subak of Guama KUAT Cooperative of Guama Subak manages a business unit carried out by Subak of Guama, one of which is an effort to breed rice seeds. The purpose of this research is to determine the communication competencies of the marketing officer of the KUAT Cooperative of Guama Subak so that the seeds produced can be sold very well and to find out how effective the marketing communication of the KUAT Cooperative of Guama Subak is on rice seed products.Communication is said to be effective if there are cognitive, affective, and conative indicators. The study took place in the KUAT Cooperative, Subak of Guama, Marga Sub-District, Tabanan Regency. The purpose of this study was to determine the communication competencies of marketing officers and determine the effectiveness of rice seed marketing communications carried out by KUAT Cooperative of Subak of Guama. The method used is a qualitative descriptive analysis method. Based on the results of the study, the communication competence of the KUAT rice seed marketing officer of Guama Subak was classified as highly competent with an average score of 23.37. The effectiveness of marketing communication is categorized as very effective with an average score of 77.3. The effectiveness of communication is shown cognitive indicators, consumers know the characteristics of rice seeds. Affective indicators, consumers are happy and interested in rice seeds and conative indicators, consumers decide to buy and use rice seeds.